Royal Tourists, Colonial Subjects and the Making of a British World, 1860–1911 - Charles Reed (Manchester University Press, 2016)
This study examines the ritual space of nineteenth-century royal tours of empire and the diverse array of historical actors who participated in them. It suggests that the varied responses to the royal tours of the nineteenth century demonstrate how a multi-centred British imperial culture was forged in the empire and was constantly made and remade, appropriated and contested. In this context, subjects of empire provincialised the British Isles, centring the colonies in their political and cultural constructions of empire, Britishness, citizenship and loyalty.An electronic edition of this book is freely available under a Creative Commons (CC BY-NC-ND) licence.